Application of K-Mean in Clustering Mapping of Underprivileged Communities - Iwan Ady Prabowo; Sri Siswanti; Lilis Wulandari (Jurnal Ilmiah SINUS, 2023)
Jatiyoso is one of 17 sub-districts in Karanganyar Regency, Central Java Province. Through this sub-district office, residents can take care of various forms of permits. There are many other functions and duties of the subdistrict office. The distance from the county seat is 30.0 km to the south. Jatiyoso is divided into 9 village areas, namely, Jatisawit, Jatiyoso, Karangsari, Petung, Tlobo, Wonokeling, Wonorejo, and Wukirsawit. With the total population of Jatiyoso District is 40,709 people. With a large population, and also a large amount of poverty. To help reduce poverty in Jatiyoso District, Jatiyoso District, an information system is needed that can explain the mapping of poverty areas in Jatiyoso Village. This information system is expected to assist the government in distributing aid to the poor. K-Means method was applied in this study to overcome the problem of grouping poor families by category.  According to the findings of study, there were 23 groups of persons with low assets (C1) and four groups of people with substantial assets (C2). The findings of the feasibility testing process with the User Acceptance Test (UAT) respondents agreed (average 95%) that the application of mapping the clustering of poor people using the k-means method can help officers in mapping the poor and facilitate the distribution of aid to the poor in Jatiyoso village